Liquid-Liquid Phase Separation of Tau Driven by Hydrophobic Interaction Facilitates Fibrillization of Tau. Issue 2 (22nd January 2021) - Lin, Yanxian; Fichou, Yann; Longhini, Andrew P.; Llanes, Luana C.; Yin, Pengyi; Bazan, Guillermo C.; Kosik, Kenneth S.; Han, Songi
Graphic abstract: Highlights: t Defining properties of tau LLPS that facilitate or protect from aggregation have been found. Tau undergoes hydrophobically driven LLPS in the presence of high [NaCl] (LLPS-HS). LLPS-HS drives canonical tau amyloid aggregation and is dissolved by 1, 6-hexanediol. LLPS-HS drives dehydration-driven hydrophobic association of tau. Tau LLPS can have different driving forces and hence have different effects on amyloid aggregation. Abstract: Amyloid aggregation of tau protein is implicated in neurodegenerative diseases, yet its facilitating factors are poorly understood. Recently, tau has been shown to undergo liquid liquid phase separation (LLPS) both in vivo and in vitro . LLPS was shown to facilitate tau amyloid aggregation in certain cases, while being independent of aggregation in other cases. It is therefore important to understand the differentiating properties that resolve this apparent conflict. We report on a model system of hydrophobically driven LLPS induced by high salt concentration (LLPS-HS), and compare it to electrostatically driven LLPS represented by tau-RNA/heparin complex coacervation (LLPS-ED). We show that LLPS-HS promotes tau protein dehydration, undergoes maturation and directly leads to canonical tau fibrils, while LLPS-ED is reversible, remains hydrated and does not promote amyloid aggregation. We show that the nature of the interaction driving tau condensation is a differentiating factor between aggregation-prone and aggregation-independent LLPS.